Interferometric excitation fluorescence lifetime imaging microscopy - Malý, Pavel; Strachotová, Dita; Holoubek, Aleš; Heřman, Petr (Nature communications, 2024)
Fluorescence lifetime imaging microscopy (FLIM) is a well-established technique with numerous imaging applications. Yet, one of the limitations of FLIM is that it only provides information about the emitting state. Here, we present an extension of FLIM by interferometric measurement of fluorescence excitation spectra. Interferometric Excitation Fluorescence Lifetime Imaging Microscopy (ixFLIM) reports on the correlation of the excitation spectra and emission lifetime, providing the correlation between the ground-state absorption and excited-state emission. As such, it extends the applicability of FLIM and removes some of its limitations. We introduce ixFLIM on progressively more complex systems, directly compare it to standard FLIM, and apply it to quantitative resonance energy transfer imaging from a single measurement.